Imprisoned in English - Wierzbicka, Anna (Oxford University Press, 2014)
Ebook from Oxford Scholarship Online; Includes bibliographical references and index; PART I: Every language draws a circle ... ; Chapter 1. Introduction: Recognising the contingency of one's own language ; Chapter 2. Naming the world or construing the world? ; Chapter 3. The givens of human life ; Chapter 4. Universal words, semantic atoms and semantic molecules ; Chapter 5. Human bodies and human minds: what is visible and what is invisible ; PART II: Emotions and values ; Chapter 6. Anglo values vs. Human values: Talking about values in a global world ; Chapter 7. Human emotions and English words: Are anger and disgust universal? ; PART III: 'Politeness' and 'cooperation' ; Chapter 8. Talking to other people: 'Politeness' and cultural scripts ; Chapter 9. Doing things with other people: 'cooperation', 'interaction' and 'obs?enie' ; PART IV: Entering other minds ; Chapter 10. Grammar and social cognition: the Hawaiians, the Dalabons, and the Anglos ; Chapter 11. Endangered languages, endangered meanings ; Chapter 12. Thinking about 'things' in Yucatec and in English ; Chapter 13. Chimpanzees and the evolution of human cognition ; PART V: Breaking down the walls of the prison ; Chapter 14. From ordinary (Anglo) English to Minimal English ; PART VI: kindred thinking across disciplines ; Preliminary remarks ; Chapter 15. Anthropology, Psychology, Psychiatry ; Chapter 16. Philosophy, Theology, Politics ; Chapter 17. Linguistics: Cognitive and cultural approaches ; Chapter 18. Bilingualism, Life writing, Translation